An exploratory factor analysis of entrepreneurship psychological readiness (EPR) instrument - Syarifah Farradinna; Nesi Syafitri; Icha Herawati; Wella Jayanti (Journal of Innovation and Entrepreneurship, 2023)
The purpose of this study was to develop an instrument for assessing psychological readiness for entrepreneurship. A well-designed measurement of entrepreneurship psychological readiness can provide early warning to policymakers, in this case the government, and provide education and funding to prospective entrepreneurs who must not only be examined physically, but also psychologically. Using Exploratory Factor Analysis (EFA) and reliability analysis, the validity and reliability of the Entrepreneurship Psychological Readiness (EPR) instrument were examined. An Exploratory Factor Analysis (EFA) found that the Entrepreneurship Psychological Readiness (EPR) instrument's eight-factor model explained 57.44% of the variance among the items. To develop a fit model, it was necessary to exclude 26 items from the questionnaire, leaving 59 items left. The factors name identified by Personal Knowledge, Personal Adversity, Committed Certain Action, Willingness to Learn, Personal Relationship to Others, Personal Growth, Passion Achieved, and Related Person Support. All of the eight-factor models have excellent reliability of 0.96.
Keywords: 650; Entrepreneurial measurement; Entrepreneurship; Factor analysis; Instrument development; Policy making; Psychological readiness